Dampak Store Atmosphere terhadap Keputusan Pembelian - Zainul Arifin (Jurnal Aplikasi Manajemen, 2012)
One of strategy which can be used is plan store atmosphere desain with form and new concept and also the creative idea develop image of shop so that make visitor feel balmy when shopping. Store image of according to view of visitor can become impeller to come into store, continueing at interaction process till the buy. This research chosen Giant hypermarket, Mall Olympic Garden of Malang Town because representing one of top brand hypermarket in Indonesia. This research aim to to know and explain impact of store atmosphere consisted of exterior, general interior, store layout, and interior of display to buy decision and also the dominant variable among its independent variable. Methodhology of research is quantitative method with type of explanatory research. Population and sample in this research is consumer shopping at Giant hypermarket, Mall Olympic Garden of Malang Town by sample as much 72 responder. Technique of sampling used is accidental sampling and analysis of data use multiple linier regression. Result of research show existence of influence among store atmosphere variable to buy decision at Giant hypermarket, Mall Olympic Garden of Malang Town either through simultan and also parsial. From all variables of store atmosphere, general of interior variable is having an effect on dominant to buy decision at Giant hypermarket, Mall Olympic Garden of Malang Town.Keywords: Store Atmosphere, exterior, general interior, store layout, interior display, buy decession.